Victims of Sexual Abuse: How Does the Law Protect Her? - Jeremya Chandra Sitorus (Universitas Negeri Semarang, 2019)
Campus sexual assault (CSA) has received unprecedented public attention lately. Sexual assault is one of the iceberg phenomena. Although men and women can be sexually assaulted, women are at greater risk. This research was aimed to describe and to classify sexual assault. The result of this research showed there are many sexual assault victims chose to remain silent and not strive for justice because imbalance of power relation, normalization of sexual assault on campus, lack of institutional support and even disciplinary act perpetrator, consequently perpetrators still remain on campus and turned compound of trauma for victims' lives. Campus intervention is important to destroy normalization of sexual assault on campus and they should take the responsibility to educate their students about consent during sexual contact.